2021
DOI: 10.17977/jptpp.v6i10.15049
|View full text |Cite
|
Sign up to set email alerts
|

Profil Miskonsepsi Siswa SMA pada Materi Gelombang Mekanik

Abstract: <p><strong>Abstract:</strong> This study aims to analyze the misconceptions of high school students on the material of mechanical waves. This study applies a survey method with the target subject of 17 students of class XI SMA in Malang Regency. The research instrument is in the form of five essay questions related to mechanical waves. Students' responses to the questions were analyzed based on the validated answer points. The results of the study showed that there were still many students wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Several studies [61][62][63][64][65][66][67][68][69][70] have identified some factors that contribute to the emergence of misconceptions in physics. First, these studies point to students' low comprehension of physical concepts, and their tendency to memorize formulas and concepts without really understanding them [61][62][63][64][65][66][67][68][69][70]. This results in a limited ability to analyze problems, and difficulties when establishing relationships between quantities and formulas.…”
Section: Causes and Effects Generated By Misconceptions In Physicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [61][62][63][64][65][66][67][68][69][70] have identified some factors that contribute to the emergence of misconceptions in physics. First, these studies point to students' low comprehension of physical concepts, and their tendency to memorize formulas and concepts without really understanding them [61][62][63][64][65][66][67][68][69][70]. This results in a limited ability to analyze problems, and difficulties when establishing relationships between quantities and formulas.…”
Section: Causes and Effects Generated By Misconceptions In Physicsmentioning
confidence: 99%
“…The role of textbooks is also a significant factor. The availability of books that present different versions of equations often hinders and slows down the understanding of the fundamentals of physics; teachers should spend more time explaining these variations [63,66].…”
Section: Causes and Effects Generated By Misconceptions In Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sure B. Not sure If the electron spin symbol used is ↑ or ↓, then the most appropriate way of arranging the electrons in the 2p 3…”
Section: Are You Sure About Your Choice?mentioning
confidence: 99%
“…The main goal of learning science is for students to experience changes in behavior and understand principles, laws, and concepts broadly and deeply [1]; [2]. For this reason, a teacher has a very important influence in creating a conducive, creative and fun learning atmosphere so that students are impressed with the lessons they receive [3]. In addition, a teacher should convey subject matter according to the right concept so that they don't just know, but really understand the material according to the right concept.…”
Section: Introductionmentioning
confidence: 99%